Ground flora of field boundary dry stone walls in the Burren, Ireland - Collier, Marcus (My University, 2020)
Despite the fact that field boundary (dry) stone walls are globally common in rural landscapes, very little research has been carried out regarding them. Dry stone walls may act as refuges for a range of plants and animals, especially in areas where conditions do not favour a high biodiversity or areas of high exposure. They may also provide connectivity via habitat corridors and may even serve as a habitat in their own right. This paper reports on a case study survey of the forb assemblages of field boundary dry stone walls in terms of species richness, biodiversity, and composition in comparison to the surrounding landscape, and aims to provide some insight into the floral ecology characteristics of dry stone walls. To accomplish this, the forbs growing in and immediately adjacent to 18 segments of dry stone wall in the Burren region of western Ireland, were surveyed. The forb assemblages growing within the walls were compared with those growing in the 0.5 m closest to the walls and those growing the areas 0.5-1.0 m on either side of the walls. The wall assemblages were shown to have lower species richness and each category of assemblage was shown to have significantly different species composition. This research indicates that the dry stone walls of the Burren may be associated with a distinct floral ecology, and therefore may act as habitat corridors in an otherwise exposed landscape.
PUBLISHED
Despite the fact that field boundary (dry) stone walls are globally common in rural landscapes, very little research has been carried out regardingthem. Dry stone walls may act as refuges for a range of plants and animals, especially in areas where conditions do not favour a high biodiversity or areas of high exposure. They may also provide connectivity via habitat corridors and may even serve as a habitat in their own right. This paper reports on a case study survey of the forb assemblages of field boundary dry stone walls in terms of species richness, biodiversity, and composition in comparison to the surrounding landscape, and aims to provide someinsight into the floral ecology characteristics of dry stone walls. To accomplish this, the forbs growing in and immediately adjacent to 18 segments of dry stone wall in the Burren region of western Ireland, were surveyed. The forb assemblages growing within the wallswere compared with those growing in the 0.5 m closest to the walls and those growing the areas 0.5-1.0 m on either side of the walls. The wall assemblages were shown to have lower species richness and each category of assemblage was shown to have significantly different species composition. This research indicates that the dry stone walls of the Burren may be associated with a distinct floral ecology, and therefore may act as habitat corridors in an otherwise exposed landscape.
Keywords: Field boundaries; Floral ecology; Corridors; Agricultural ecology; Forb; Limestone pavement; Smart & Sustainable Planet; BIODIVERSITY; Biodiversity and Conservation; Biodiversity distribution; Burren; ECOLOGY; FLORA; Flora of Ireland; NOVEL ECOSYSTEMS; Plant Biodiversity; Stone wall ecology; dry stone wall; hedgerow ecology; landscape ecology; Environment and housing